Analisis Penerapan PSAK 73 atas Sewa Aset Produktif terhadap Laporan Keuangan pada PT. ABC - Nafsia, Siti Nurhayati; Ayu, Astri (Ekonomis: Journal of Economics and Business, 2025)
This research aims to determine the application of PSAK (Statement of Financial Accounting Standards) 73 on the lease of productive assets to financial reports. This type of research is qualitative research, and the subjects of this research are PT actors. ABC in Palembang City. This research uses descriptive analysis methods, while data collection techniques use interviews, observation and documentation. The results of this research indicate that the application of PT ABC's accounting treatment when viewed from recognition, measurement, presentation and disclosure is in accordance with PSAK 73.